Drug-induced optic neuropathy. (June 2022) - Horwitz, Anna; Horwitz, Henrik
Abstract : Summary: Drug-induced optic neuropathy is an understudied subject, and most of the evidence is based on case-reports. Amiodarone, ciprofloxacin, disulfiram, and sildenafil have been associated with optic neuropathy and their use is relatively prevalent. We therefore set out to investigate the strength of this association. In this nationwide cohort, we identified all incident users of the four drugs studied during the period 1 January 1999 to 31 December 2018. We then investigated their incidence of optic neuropathy in the year prior to prescription and in the year following We found that the risk of being diagnosed with optic neuropathy was 2.27 [95% confidence interval (1.29–4.00)] higher times during amiodarone therapy than in the year prior to prescription, but for the three other drugs we found no certain association. This study revealed a weak association between optic neuropathy and amiodarone; however, we were unable to confirm any association with ciprofloxacin, sildenafil, and disulfiram.